1992
DOI: 10.1056/nejm199207303270501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Uncultured Bacillus of Whipple’s Disease

Abstract: We have identified the uncultured bacillus associated with Whipple's disease. The phylogenetic relations of this bacterium, its distinct morphologic characteristics, and the unusual features of the disease are sufficient grounds for naming this bacillus Tropheryma whippelii gen. nov. sp. nov. Our findings also provide a basis for a specific diagnostic test for this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
542
1
31

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,095 publications
(584 citation statements)
references
References 36 publications
10
542
1
31
Order By: Relevance
“…En l'absence d'identité significative avec les espèces bacté-riennes déjà recensées, une nouvelle espèce bactérienne peut être décrite et positionnée dans l'arbre phylogénétique construit à partir des séquences d'ADNr 16S connues. La puissance de cette approche a été illustrée par l'identification de Tropheryma whippelii, espèce bactérienne associée à la maladie de Whipple [14], et alors non cultivable, ou de Bartonella henselae, associée à l'angiomatose bacillaire [15]. L'utilisation de cette technique à partir des échantillons intestinaux congelés de cette patiente a conduit à la mise en évi-dence de séquences appartenant à l'espèce Campylobacter jejuni [13].…”
Section: La Cible Thérapeutique De L'ezetimibe : Npc1-l1unclassified
“…En l'absence d'identité significative avec les espèces bacté-riennes déjà recensées, une nouvelle espèce bactérienne peut être décrite et positionnée dans l'arbre phylogénétique construit à partir des séquences d'ADNr 16S connues. La puissance de cette approche a été illustrée par l'identification de Tropheryma whippelii, espèce bactérienne associée à la maladie de Whipple [14], et alors non cultivable, ou de Bartonella henselae, associée à l'angiomatose bacillaire [15]. L'utilisation de cette technique à partir des échantillons intestinaux congelés de cette patiente a conduit à la mise en évi-dence de séquences appartenant à l'espèce Campylobacter jejuni [13].…”
Section: La Cible Thérapeutique De L'ezetimibe : Npc1-l1unclassified
“…Wilson (642). Recently, Relman and colleagues reported a technique in which oligonucleotide primers specific for the Whipple's disease bacillus were used in a PCR to amplify sequences of bacterial 16S rRNA directly from infected tissues (469). Following a comparative 16S rRNA sequence analysis, they concluded that the disease is caused by an as-yet-uncultured and uncharacterized actinomycete, which they named Tropheryma whippelii.…”
Section: Taxonomy and Microbiologic Aspectsmentioning
confidence: 99%
“…The elucidation of the cause of new and emerging infectious diseases is more challenging and often even impossible when using only conventional methods. The shift from phenotypic to molecular methods has largely improved the identification process and facilitated the detection of yet unknown microorganisms (Relman et al, 1992;Roads et al, 2012). The final product of this ongoing evolution in diagnostics is the implementation of mass spectrometry for fast and accurate identification of microorganisms.…”
Section: Resultsmentioning
confidence: 99%